2010
DOI: 10.1002/mds.23257
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic diagnosis of idiopathic REM sleep behavior disorder

Abstract: The presence of either excessive tonic chin EMG activity during REM sleep, or excessive phasic submental or limb EMG twitching is required to diagnose REM sleep behavior disorder (RBD). The aim was to identify cut-off values and to assess the sensitivity and specificity of these values taken separately or combined to diagnose idiopathic RBD patients. Eighty patients presenting with a clinical diagnosis of idiopathic RBD and 80 age- and gender-matched normal controls were studied in the sleep laboratory. Receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
201
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(209 citation statements)
references
References 23 publications
7
201
0
1
Order By: Relevance
“…For example, previous studies have revealed that RBD patients exhibit normal atonia and lack of phasic activity on mentalis recordings but have increased phasic activity in the upper limbs. 35 As we did not record data from the upper extremities, we were not able to capture this phasic activity. In future studies, detailed EMG recordings could be used in patients with suspected RBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies have revealed that RBD patients exhibit normal atonia and lack of phasic activity on mentalis recordings but have increased phasic activity in the upper limbs. 35 As we did not record data from the upper extremities, we were not able to capture this phasic activity. In future studies, detailed EMG recordings could be used in patients with suspected RBD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we did not capture upper extremity EMG data, as is now recommended in possible RBD patients. 35 Despite these limitations, the results may be helpful in designing further studies to differentiate sleep problems in ET and PD.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnographic diagnosis of RBD and RWA was performed along international recommendations [11]: We used following references values: a 30-second epoch was scored as tonic if chin EMG activity was present for more than 50% of the epoch; phasic epochs were scored in response of 2-second mini-epochs (within 30-second REM sleep epoch) with bursts of EMG activity; RWA was ascertained if tonic chin EMG density was greater than approximately 30% and / or a phasic chin EMG density was greater than approximately 15% of total REM sleep time was assessed as REM sleep without atonia (RWA). RWA with complex movements or vocalization as assessed by time-locked video was defined as manifest RBD.…”
Section: Methodsmentioning
confidence: 99%
“…1 The PSG criteria of RBD was according to a published method. 13,14 Patients were allowed to be prescribed levodopa (except controlled-release levodopa or > 5 daily doses of immediate-release levodopa), anticholinergic agents, entacapone, monoamine oxidase-B inhibitors or amantadine, provided that doses were stable for ≥ 28 days prior to baseline assessment and stable during the trial. Exclusion criteria were dementia, hallucinations, psychosis, current or previous treatment with other dopamine agonists, or antidopaminergic agents.…”
Section: Subjectsmentioning
confidence: 99%
“…VPSG staging and scoring followed the American Academy of Sleep Medicine (AASM) guidelines, 16 with the exception that REM sleep stage was scored based only on electroencephalogram and electoroculograms 14 to account for the frequent of occurrence of REM sleep without atonia (RWA) in PD. During REM sleep, we calculated the REM density, the phasic and tonic electromyographic activity in the submentalis muscle, 17 and the percentage of REM sleep with abnormal behaviors, 7 as previously reported.…”
Section: Nocturnal Video-polysomnographymentioning
confidence: 99%